Strategies to reduce mycotoxin levels in maize during storage: A review - Chulze, Sofia Noemi (2010)
Maize (Zea mays L.) is one of the main cereals as a source of food, forage and processed products for industry. World production is around 790 million tonnes of maize because as a staple food it provides more than one-third of the calories and proteins in some countries. Stored maize is a man-made ecosystem in which quality and nutritive changes occur because of interactions between physical, chemical and biological factors. Fungal spoilage and mycotoxin contamination are of major concern. Aspergillus and Fusarium species can infect maize pre-harvest, and mycotoxin contamination can increase if storage conditions are poorly managed. Prevention strategies to reduce the impact of mycotoxin in maize food and feed chains are based on using a hazard analysis critical control point systems (HACCP) approach. To reduce or prevent production of mycotoxins, drying should take place soon after harvest and as rapidly as feasible. The critical water content for safe storage corresponds to a water activity (aw) of about 0.7. Problems in maintaining an adequately low aw often occur in the tropics where high ambient humidity make the control of commodity moisture difficult. Damage grain is more prone to fungal invasion and, therefore, mycotoxin contamination. It is important to avoid damage before and during drying, and during storage. Drying maize on the cob before shelling is a very good practice. In storage, many insect species attack grain and the moisture that can accumulate from their activities provides ideal conditions for fungal activity. To avoid moisture and fungal contamination, it is essential that the numbers of insects in stored maize should be kept to a minimum. It is possible to control fungal growth in stored commodities by controlled atmospheres, preservatives or natural inhibitors. Studies using antioxidants, essential oils under different conditions of aw, and temperature and controlled atmospheres have been evaluated as possible strategies for the reduction of fungal growth and mycotoxin (aflatoxins and fumonisins) in stored maize, but the cost of these treatments is likely to remain prohibitive for large-scale use.